The Urgency Of Kvisoft Flipbook Maker-Based Media Development Reviewed By Literature Review - Rini, Respito; Irfandi, Irfandi; Yuhelman, Nofri (Sean Institute, 2023)
The development in the 21st century is the development of information technology where its development has a huge impact, so teachers and students are required to have skills in using technology. The kvisoft flipbook maker application is one example. This application is considered interesting because it displays a rotating publish, which resembles a real book. The method used in this research is the literature review method. This study aims to examine the urgency of developing the Kvisoft flipbook maker application in learning by reviewing 10 R&D articles, with 6 ADDIE model journal articles, 2 Borg & Gall R&D model journal articles, 1 Hannafin and Peck model journal article, and Plomp development model journal, expert validation shows very satisfactory results from these 10 articles, where the validation score of the material expert is 90% and the media expert is 88% and the results of the student response questionnaire also show very good results, namely 88%. This shows that the use of the Kvisoft flipbook maker application is very helpful for students in understanding the material.